A Study for Visual Realism of Designed Pictures on Computer Screens by Investigation and Brain-Wave Analyses. - Lan-Ting Wang; Kun-Chou Lee (Perceptual & Motor Skills, 2016)
In this article, the visual realism of designed pictures on computer screens is studied by investigation and brain-wave analyses. The practical electroencephalogram (EEG) measurement is always time-varying and fluctuating so that conventional statistical techniques are not adequate for analyses. This study proposes a new scheme based on "fingerprinting" to analyze the EEG. Fingerprinting is a technique of probabilistic pattern recognition used in electrical engineering, very like the identification of human fingerprinting in a criminal investigation. The goal of this study was to assess whether subjective preference for pictures could be manifested physiologically by EEG fingerprinting analyses. The most important advantage of the fingerprinting technique is that it does not require accurate measurement. Instead, it uses probabilistic classification. Participants' preference for pictures can be assessed using fingerprinting analyses of physiological EEG measurements.